Fragile-X: neuropsychological test performance, CGG triplet repeat lengths, and hippocampal volumes. - Jäkälä, P (1997)
We compared cognitive performance and hippocampal volumes using magnetic resonance imaging (MRI) in adult fragile-X [fra(X)] males and females with either premutation (pM) or full mutation (fM) (n = 10 in all groups). Cognitive performance of fM males in the Wechsler Adult Intelligence Scale-Revised was worse than that of pM males, and the deficits in fM females were qualitatively similar, but less severe. In a visual memory test, both fM groups were impaired. In a list learning test, fM males were impaired in the learning phase and in delayed recognition. In a logical memory test, fM males and females were not significantly different from pM subjects. Hippocampal volumes normalized for intracranial or brain area did not significantly differ between fM and pM groups. However, positive correlations between left normalized hippocampal volumes and performance in many delayed memory tests observed in pM subjects were absent in fM subjects. Furthermore, in > 50% of the fM subjects, nonspecific changes, such as enlargement of ventricles and perivascular spaces, focal hyperintensities in temporal pole white matter, and/or subjectively assessed atypical appearance of hippocampal morphology, were observed in MRI. The data suggest minor abnormalities in temporal lobe structures in adult fra(X) subjects with fM.